Cryptosporidiosis in non-human primates - Diniz Garcia, Sérgio [UNESP]; Mendes, Bruno Criado de Araújo [UNESP]; Bruno, Débora Barbosa [UNESP]; Borégio, Jaqueline da Silva; Dastre, Marcela; Borges, Vinícius Camarena; Bresciani, Katia Denise Saraiva [UNESP] (My University, 2018)
The criptosporidiosis is known since 1907, but there is no much data compilation about it. 152 animal species have been described with this parasite. With all the researches found, it is necessary a review about the disease, for a great understanding about the Cryptosporidium. This research has the purpose to show all the information found in a systematic review of articles about cryptosporidiosis in non-human primates. For a better understanding, this article describe the historic, taxonomy, epidemiology cycle, clinical signs, diagnostic, treatment and prevention.
Keywords: Cryptosporidiosis; Cryptosporidium; Monkeys; Protozoan; Zoonosis and primates